Influence of Algal Based Protein Nanoparticles Loading on Antibacterial Activity, In Vitro Drug Release and Cytotoxicity of Cephalosporine Derivative (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: In this study, algal based protein, such as phycocyanin nanoparticles loaded cephalosporine derivative cefotaxime nano drug conjugate, has been prepared for the improved antibacterial activity, in vitro drug release and cytotoxicity. Materials and Methods: Nano drug conjugate was prepared by simple coacervation technique. Method for preparation of nano drug conjugate was optimized with various parameters such as pH, ethanol to phycocyanin ratio, and crosslinking time. Well diffusion assay and turbidimetric assay were carried out to determine the antibacterial activity. Effect of nanoparticles loading on drug release was studied by continuous dialysis method, and cytotoxicity was determined by methylthiazolyldiphenyl-tetrazolium bromide (MTT) assay using Vero cell line. Results and Discussion: Nano drug conjugate was prepared using the optimized conditions at pH were 8.0 pH, 6:1 the ethanol to phycocyanin ratio, 10 h. Crosslinking time and the nanospheres formed were characterized using scanning electron microscopy which showed a particle size of nanosphere in the range of 70-90 nm and Fourier transform infrared spectroscopy revealed the possible functional groups of nano drug conjugate. Nano drug conjugate showed distinct drug loading, entrapment efficacy, and release profile. Antibacterial activity against human pathogenic bacterial strains revealed effective inhibition at the least concentration. Biocompatibility studies using Vero cell line adopting MTT assay was confirmed by showing maximum cell viability. Conclusion: This study would suggest the possible utilization of phycocyanin nanoparticles loaded cefotaxime nano drug conjugate as an antibacterial agent against pathogenic bacteria.